The gut–microbiota–brain changes across the liver disease spectrum - Higarza, Sara G.; Arboleya, Silvia; Arias, Jorge L.; Gueimonde, Miguel; Arias, Natalia (Frontiers in Cellular Neuroscience, 2022)
Gut microbiota dysbiosis plays a significant role in the progression of liver disease, and no effective drugs are available for the full spectrum. In this study, we aimed to explore the dynamic changes of gut microbiota along the liver disease spectrum, together with the changes in cognition and brain metabolism. Sprague–Dawley rats were divided into four groups reflecting different stages of liver disease: control diet (NC); high-fat, high-cholesterol diet (HFHC), emulating non-alcoholic steatohepatitis; control diet + thioacetamide (NC + TAA), simulating acute liver failure; and high-fat, high-cholesterol diet + thioacetamide (HFHC + TAA) to assess the effect of the superimposed damages. The diet was administered for 14 weeks and the thioacetamide was administrated (100 mg/kg day) intraperitoneally over 3 days. Our results showed changes in plasma biochemistry and liver damage across the spectrum. Differences in gut microbiota at the compositional level were found among the experimental groups. Members of the Enterobacteriaceae family were most abundant in HFHC and HFHC + TAA groups, and Akkermansiaceae in the NC + TAA group, albeit lactobacilli genus being dominant in the NC group. Moreover, harm to the liver affected the diversity and bacterial community structure, with a loss of rare species. Indeed, the superimposed damage group (HFHC + TAA) suffered a loss of both rare and abundant species. Behavioral evaluation has shown that HFHC, NC + TAA, and HFHC + TAA displayed a worsened execution when discriminating the new object. Also, NC + TAA and HFHC + TAA were not capable of recognizing the changes in place of the object. Furthermore, working memory was affected in HFHC and HFHC + TAA groups, whereas the NC + TAA group displayed a significant delay in the acquisition. Brain oxidative metabolism changes were observed in the prefrontal, retrosplenial, and perirhinal cortices, as well as the amygdala and mammillary bodies. Besides, groups administered with thioacetamide presented an increased oxidative metabolic activity in the adrenal glands. These results highlight the importance of cross-comparison along the liver spectrum to understand the different gut–microbiota–brain changes. Furthermore, our data point out specific gut microbiota targets to design more effective treatments, though the liver–gut–brain axis focused on specific stages of liver disease.